Analysis of Slip Plane Using Geoelectric Data in Pancor Dao Central Lombok - Ulfah, Syarifatul; Winardi, Agus (Universitas Trunojoyo Madura, 2025)
Landslide are one of the disasters that occur in sloping areas. It occurs very often when the intensity of rainfall is high. Apart from that, it occurs in an area known as a slip area. The slip area is characterized by contrasting rock resistivity values. This research aims to determine the resistivity value of the soil indicated as a sliding area using the geoelectric method with a dipole-dipole configuration. A dipole-dipole configuration is used to get a deeper penetration value compared to other configurations. Field data collection was carried out on 3 tracks with a research area of around 1,000 m2. Based on the results of data processing using 2D Res2divn inversion, the soil resistivity value is obtained which is indicated as a slip plane. The soil resistivity value indicated as a slip plane on 3 line, namely resistivity value on line 1 of 973 Ωm - 2067 Ωm, line 2 of 1202 Ωm - 3167 Ωm, line 3 of 618 Ωm – 1391 Ωm which is classified as a type of silt clay soil. the results show that the depth of slip plane on the third line is deeper than the first line and second line. From the soil resistivity values, it represents the slip plane. And the depth of slip plane on 3 line, namely at a depth of 8.53 m - 12.7 m for the first line, 5.13 - 16.3 m for the second line, and 1.71 - 17 m for the third line. And categorized as shallow to deep slip plane types.